2015
DOI: 10.5897/ajpp2015.4316
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic activity of medicinally important leaf of Diplazium esculentum

Abstract: The use of medicinal plants in modern medicine suffers from the fact that though hundred of plants are used in the world to prevent or to cure disease, scientific evidence in term of modern medicine is lacking in most cases. However, today it is necessary to provide scientific proof as to whether or not it is justified to use a plant or its active constituents. Pain and inflammation are considered one of the oldest known diseases of mankind and affects a large population of the world, unsatisfactory progress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Several studies have reported the activities of D. esculentum (Retz.) Sw. extract such as antibacterial [30,31], antioxidant [10,32,33,34], analgesic [20], hepatoprotective [35], anti-inflammatory [35], and anthelmintic [13]. Traditionally, some of its uses as a medicinal plant were as insecticides and repellent of insects and pests [10,13,20] 2).…”
Section: Phytochemical Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported the activities of D. esculentum (Retz.) Sw. extract such as antibacterial [30,31], antioxidant [10,32,33,34], analgesic [20], hepatoprotective [35], anti-inflammatory [35], and anthelmintic [13]. Traditionally, some of its uses as a medicinal plant were as insecticides and repellent of insects and pests [10,13,20] 2).…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Sw. extract such as antibacterial [30,31], antioxidant [10,32,33,34], analgesic [20], hepatoprotective [35], anti-inflammatory [35], and anthelmintic [13]. Traditionally, some of its uses as a medicinal plant were as insecticides and repellent of insects and pests [10,13,20] 2). The results showed a strong activity with LC50 value of 149.279 ppm.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
See 1 more Smart Citation